The History of Rugby in Spain. Part I. From the beginnings of the game to the 1923 - Xavier Torrebadella-Flix (Federación Extremeña de Balonmano; University of Extremadura, 2020)
Rugby was one of the sports to arrive late in Spain. Documentary research centres on primary bibliographical sources and historical press shows new data about the origins of the sport and the difficulties encountered during its initial years from 1894 to 1923. While rugby did not attract the popularity of other team sports, its peak in Barcelona served as propaganda for the spread of the game to other regions of Spain. Rugby also maintained very particular features which differentiated it from the sport of choice in the country: football.